The Role of Managerial Control in Achieving Organizational Development: Applied Study in Palestine’s Public Universities - Sweiss, Mohammad (The Arab Journal of Administration, 2020)
The aim of this study is to recognize the availability of managerial control components and organizational development achievements in the governmental universities in Palestine. By examining the relationship between managerial control components (Top Management support, the availability of tools and facilities, employees acceptance, self control, positive control) and organizational development achievements. This study proposes some hypothesis and used questionnaire as a research tool. The questionnaire were distributed to 210 employees and collected from 194 employees. The results of this study report a high level of managerial control (79.720%), in addition, achieving competitive advantage reaches to (75.601%). There is appositive relationship between managerial control and organizational development, The results reported (%61.70) of chang in organizational development based on the managerial control. There is no statistical differences between respondents regarding to managerial control and organizational development achievements based on gender, university, age, academic qualification. But there is a statistical differences based on the years of experience. Based on the results study recommendations are as the following: The importance of applying control management systems in Palestinian Universities, and improve the current system to solve the issues and the gaps. The importance to develop the managerial control tools to benefit from the objective that is designed to increase the level of reliance on the control of work. Find and meet the material needs and requirements to support the continuous development of technological and technical infrastructure.